1981
DOI: 10.1111/j.1432-1033.1981.tb05698.x
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Thallous Ions by Mitochondria is Stimulated by Nonactin but not by Respiration Alone

Abstract: Nonrespiring rat-liver mitochondria swell in media containing high concentrations of thallous nitrate, indicating passive penetration of Tl'. This swelling could be further stimulated by 10 nM or more nonactin while even 1 pM valinomycin was without effect. Nonactin was also much more potent than valinomycin in stimulating swelling of respiring mitochondria in the presence of thallous acetate. It is evident that nonactin acts as a potent ionophore of T1' able to promote both the passive and energized uptake of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(44 citation statements)
references
References 23 publications
0
43
1
Order By: Relevance
“…Nevertheless, despite their increased permeability, the energized mitochondria were rapidly contracted to the initial volume even in the medium with 50 mM TlNO 3 and nonactin ( Figure 1B), which agrees well with the minimal inhibition of DNP-stimulated respiration in the medium with 50 mM Tl + and nonactin ( Figure 3C). Swelling of energized mitochondria increased in the series with 10-50 mM Tl acetate medium (Figure 2A), which was earlier recorded only with 25 mM Tl acetate medium [4,7]. It is known that nonactin, a cyclic ionophore, has a high chemical affinity to Tl + ions [4] and accelerates influx of Tl + in the mitochondrial matrix [10].…”
Section: Effect Of Nonactin On the Transport Of Tl + Via The Inner MImentioning
confidence: 72%
See 4 more Smart Citations
“…Nevertheless, despite their increased permeability, the energized mitochondria were rapidly contracted to the initial volume even in the medium with 50 mM TlNO 3 and nonactin ( Figure 1B), which agrees well with the minimal inhibition of DNP-stimulated respiration in the medium with 50 mM Tl + and nonactin ( Figure 3C). Swelling of energized mitochondria increased in the series with 10-50 mM Tl acetate medium (Figure 2A), which was earlier recorded only with 25 mM Tl acetate medium [4,7]. It is known that nonactin, a cyclic ionophore, has a high chemical affinity to Tl + ions [4] and accelerates influx of Tl + in the mitochondrial matrix [10].…”
Section: Effect Of Nonactin On the Transport Of Tl + Via The Inner MImentioning
confidence: 72%
“…However, it was recently reported that the K + /H [4,36,37], it can be suggested that both release of Tl + from energized mitochondria swollen in the TlNO 3 medium ( Figure 1A) and swelling of nonenergized mitochondria in the Tl acetate medium (Figure 2A) are likely to occur via the mitochondrial K + /H + exchanger, but not a special Tl + /H + exchanger as postulated by Saris et al [3]. On the other hand, the faster swelling of nonenergized mitochondria in the medium with nonactin and 50-75 mM of TlNO 3 ( Figure 1B) or 50 mM of Tl acetate ( Figure 2B) and some retardation in the contraction of energized mitochondria swollen in the medium with TlNO 3 and nonactin ( Figure 1B) are likely to be due to an increase of permeability of the inner mitochondrial membrane to Tl + ions in the presence of nonactin [4,10]. Nevertheless, despite their increased permeability, the energized mitochondria were rapidly contracted to the initial volume even in the medium with 50 mM TlNO 3 and nonactin ( Figure 1B), which agrees well with the minimal inhibition of DNP-stimulated respiration in the medium with 50 mM Tl + and nonactin ( Figure 3C).…”
Section: Effect Of Nonactin On the Transport Of Tl + Via The Inner MImentioning
confidence: 96%
See 3 more Smart Citations